Factors Influencing the Reintroduction of Border Control (Academic Journal of Internal Affairs, 2019)
One of the significant acquis of the Schengen idea is that persons, vehicles and consignments are allowed to move freely, without control at the Member States’ internal borders. In case the control mechanism of the Schengen external borders does not grant the security of the area, or a Member State decides to temporarily reintroduce border control at its Schengen internal borders in order to protect its own security, both staff and technology related implications has to be expected. The main purpose of the study is to examine the time, place, content, human resource needs and technical and IT background of the control.
Keywords: temporary reintroduction of border control; technical assistance; content of control; security of the Schengen Area